(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Patients with end-stage renal disease (ESRD) have a wide range of skin manifestations, ranging from benign conditions, such as xerosis, pruritus, color changes, and half-and-half nails, to life-threatening calciphylaxis. Comprehensive knowledge of the various changes in appropriate symptomatic relief is imperative in these patients’ management process. Thus, we assessed the pattern of cutaneous comorbidities among patients with ESRD undergoing hemodialysis. Methods: A descriptive hospital-based cross-sectional study was conducted at the dialysis center of Jerash Governmental Hospital, Jerash, Jordan, from August 2022 to September 2022. A total of 158 patients with ESRD of adult age and gender were included in our study. Results: Out of the 158 participants, 80 (50.6%) were male, and 78 (49.4%) were female. The leading cause of ESRD was hypertension in 77 participants (48.7%), followed by diabetes mellitus in 36 patients (22.8%). Among the participants, the two most common skin changes reported were skin dryness in 63 participants (39.87%), followed by uremic pruritus in 49 participants (31.01%). Hypertension was the most common cause of ESRD. Xerosis was the most common cutaneous comorbidity, followed by uremic pruritus and hyperpigmentation. Conclusion: Hemodialysis patients can have various cutaneous comorbidities that have significant negative effects on their quality of life. Therefore, health professionals need to be aware of these manifestations so that they can advise patients on prophylactic measures to take to improve skin care and promptly recognize and treat serious skin conditions associated with hemodialysis, thus reducing morbidity and mortality.